Straightforward Synthesis of the Pentasaccharide Repeating Unit of the O-Antigenic Polysaccharide from the Enteropathogenic Escherichia coli O142 - Jana, Swapan Kumar; Shit, Pradip; Misra, Anup Kumar (Synthesis, 2022)
The pentasaccharide repeating unit rich in 2-acetamido sugars corresponding to the O-antigenic polysaccharide from enteropathogenic Escherichia coli (E. coli) has been synthesized as the p-methoxyphenyl glycoside in excellent yield using a sequential glycosylation strategy. Regioselective glycosylation, use of a single monosaccharide intermediate in multiple glycosylations, and use of thioglycosides as glycosyl donors in the presence of a combination of N-iodosuccinimide (NIS) and perchloric acid supported over silica (HClO4–SiO2) are key components of the synthetic strategy. All glycosylation reactions were high-yielding with excellent stereochemical outcome.
Keywords: carbohydrates; glycosylation; glycosides; oligosaccharides; synthesis; E. coli